Information seeking and students studying for professional careers: the cases of engineering and law students in Ireland - Gillian Kerins; Ronan Madden; Crystal Fulton (Information Research: An International Electronic Journal)
This paper reports the results of two empirical studies which explored the information seeking behaviour of engineering and law students in Ireland. Findings reveal similar patterns in the information seeking behaviour between students studying to become professionals and information seeking patterns of these groups identified in Leckie et al.'s model. Students learned their information seeking strategies, including effective and less effective approaches, from educators and continuing mis-perceptions of libraries and information professionals. The studies suggest that engineering and law students in Ireland could benefit from greater information literacy training and awareness, enabling them to acquire the information skills they need to function effectively and efficiently in their future professional work lives.